Should Initial Surveillance of Vestibular Schwannoma Be Abandoned? - Eljamel, Sarah (Thieme Medical Publishers, 2011)
Early diagnosis of vestibular schwannoma (VS) has increased in recent years because of increased longevity and availability of magnetic resonance imaging (MRI). Initial conservative radiological surveillance is often requested by patients and physicians to establish whether these tumors are growing before embarking on intervention. Initial observation of at least 1 year in all small VS was therefore recommended by some authors. We evaluated our prospective skull base database of VSs that were managed with initial radiological surveillance to establish when this policy should be abandoned and what predicts future growth. Fifty-four consecutive patients with VS in our institution who were managed by initial yearly MRI scanning were studied. The MRI data were collected prospectively and analyzed by Kodak CareStream viewing software where VS maximum diameters in three perpendicular planes and volume were calculated. One patient was excluded from the analysis as he had only one MRI follow-up. The median age of the 53 patients was 59 years (range, 26 to 86 years), 25 were males and 28 were females, and 33 were under 65 years of age; 18 VSs were extracanalicular, 18 were intracanalicular, and 17 extended both inside and outside the canal; 21 VSs were 1.2 cm(3) or less, 22 were 1.2 to 4 cm(3), and the rest were >4 cm(3). Using volumetric analysis, 29.72% of conservatively managed VS grew by at least 2 mm per year, and 70.82% did not grow in 5 years. Age, gender, symptoms, and side did not predict future growth. However, growth in the first year was a strong predictor of future growth (p < 0.001) and initial volume was also a strong predictor of future growth (p < 0.05). Twenty-nine percent of observed VSs grew by at least 2 mm per year in the first 5 years of surveillance. As the growth rate is slow, initial radiological surveillance is justified in elderly patients and patients with small VSs and nonserviceable hearing. Growth in the first year was a strong predictor of future growth. The reported treatment effect should be interpreted in the light of 70.24% of VSs that either shrink or do not change in the first 5 years.